Examining mental health knowledge, stigma, and service use intentions among Royal Canadian Mounted Police cadets - Andrews, Katie L.; Jamshidi, Laleh; Shields, Robyn E.; Teckchandani, Taylor A.; Afifi, Tracie O.; Fletcher, Amber J.; Sauer-Zavala, Shannon; Brunet, Alain; Krätzig, Gregory P.; Carleton, R. Nicholas (Frontiers in Psychology, 2023)
Background Royal Canadian Mounted Police (RCMP) officers experience an elevated risk for mental health disorders due to inherent work-related exposures to potentially psychologically traumatic events and occupational stressors. RCMP officers also report high levels of stigma and low levels of intentions to seek mental health services. In contrast, very little is known about the levels of mental health knowledge and stigma of RCMP cadets starting the Cadet Training Program (CTP). The current study was designed to: (1) obtain baseline levels of mental health knowledge, stigma against peers in the workplace, and service use intentions in RCMP cadets; (2) determine the relationship among mental health knowledge, stigma against peers in the workplace, and service use intentions among RCMP cadets; (3) examine differences across sociodemographic characteristics; and (4) compare cadets to a sample of previously surveyed serving RCMP. Methods Participants were RCMP cadets (n = 772) starting the 26-week CTP. Cadets completed questionnaires assessing mental health knowledge, stigma against coworkers with mental health challenges, and mental health service use intentions. Results RCMP cadets reported statistically significantly lower levels of mental health knowledge (d = 0.233) and stigma (d = 0.127), and higher service use intentions (d = 0.148) than serving RCMP (all ps < 0.001). Female cadets reported statistically significantly higher scores on mental health knowledge and service use and lower scores on stigma compared to male cadets. Mental health knowledge and service use intentions were statistically significantly positively associated. For the total sample, stigma was inversely statistically significantly associated with mental health knowledge and service use intentions. Conclusion The current results indicate that higher levels of mental health knowledge were associated with lower stigma and higher intention to use professional mental health services. Differences between cadets and serving RCMP highlight the need for regular ongoing training starting from the CTP, designed to reduce stigma and increase mental health knowledge. Differences between male and female cadets suggest differential barriers to help-seeking behaviors. The current results provide a baseline to monitor cadet mental health knowledge and service use intentions and stigma as they progress throughout their careers.